PENATALAKSANAAN ANAK DEMAM OLEH ORANG TUA DI PUSKESMAS KEMBARAN I BANYUMAS - Etika Dewi Cahyaningrum (Viva Medika, 2016)
Fever in children is a condition that often causes anxiety, stress and phobias for parents.When a child has a fever parents often make efforts to reduce fever children. During this time theeffort is often done to reduce fever children parents are giving febrifuge/ antipyretic. Reduce feverand fever control in children can be done in various ways, including by pharmacological andphysical (non-pharmacological) that is by the use of heat energy by conduction and evaporationmethod. Conduction and evaporation method can be done with warm compresses and also can bedone with traditional medicine. This study aims to describe the management of febrile children byparents. This research uses descriptive quantitative research methods. Sampling in this studyusing total sampling. Samples were all parents who have children with a fever at PuskesmasKembaran I Banyumas period from May 2016 that a total of 106 respondents. The type of data inthis study are primary data obtained from questionnaires measuring instrument. Processing of thedata include: editing, coding, tabulating, data entry, and cleaning. Analysis of the data used is theunivariate analysis. The analysis showed that the majority of parents do the management of febrile childrenwith pharmacological means that a number of 53 respondents (50%). Outcomes to be generated isin the form of scientific publications is not accredited national journal (ISSN) is Viva MedikaSTIKES Harapan Bangsa Purwokerto, and science for health workers in health centers IKembaran Banyumas in the form of Power Point (print) about the study results. Keywords: management of the child's fever